Aerosol chemistry and soluble iron in Tenerife, Barbados and Miami in summer 2015 - dataset ... - Rodríguez, Sergio; Prospero, J. M.; López-Darias, Jessica; García, M. Isabel; Zuidema, Paquita; Nava, Silvia; Lucarelli, Franco; Gaston, Cassandra J.; Galindo, Luis; Sosa, Elisa (CSIC - Estación Experimental de Zonas Áridas (EEZA), 2020)
This dataset contains data of aerosol chemistry and soluble iron collected in Tenerife, Barbados and Miami in summer 2015 within the frame of the project AEROATLAN (reference CGL2015-66299-P), funded by the Minister of Economy and Competitiveness of Spain and by the European Regional Development Fund. ...